Correlates of smoking among youth: the role of parents, friends, attitudes/beliefs, and demographics. Issue 1 (December 2016) - Dietz, Noella; Arheart, Kristopher; Sly, David; Lee, David; McClure, Laura
Abstract Background Family engagement has been shown to play a crucial role in youth cigarette use prevention and uptake. We examine cross-sectional and longitudinal data to determine whether changes in parental monitoring factors influence changes in smoking susceptibility. Methods Two cross-sectional surveys of Florida youth (12–17 years) were conducted in 2009, with a follow-up survey in 2010. Multivariable analyses examined demographics, parent characteristics, family engagement, and parental monitoring on youth susceptibility to smoke. Results Cross-sectional data show eating together 6+ times/week and doing something for fun 5+ times/week were related to an increased likelihood of Very Low and decreased likelihood of High susceptibility, respectively. Parental monitoring factors and parents tell on a friend who smokes was significantly related to having Very Low susceptibility in both surveys. Mother's education, parent smokes, family engagement factors, and parental monitoring were significant in both survey rounds. Longitudinal analyses showed change in eating together did not significantly affect the odds of change in smoking susceptibility; however, change in the frequency of doing things for fun with a parent showed decreased odds of susceptibility (OR = .63 [.49–.82]), opposite of the hypothesized direction. Lastly, as youth aged, they were more likely to experience a greater odds of decreased susceptibility (OR14-15y = 1.47 [1.08–1.99] and OR≥16y = 1.40 [1.05–1.84], respectively) and less likely to experience an increased odds of susceptibility (OR14-15y = .65 [.49–.86] and OR≥16y = .72 [.56–.93], respectively). Conclusions We found mixed results for family engagement and parental monitoring on changes in youth smoking susceptibility. Cross-sectional data showed general associations in the expected direction; however, longitudinal analyses showed family engagement variables had significance, but in the opposite hypothesized direction.